Caste stone formation in the MgO-H2O-organo system – Effect of citric, malic or acetic acid and MgO reactivity on type and composition of castables. (December 2021) - Gerger, Sabrina; Baldermann, Andre; Dietzel, Martin
Graphical abstract: Abstract: Consolidation of MgO castables by organic acids is a common technique for various applications, but the distinct hardening mechanisms of caste stone formation are still poorly constrained. In this study, the individual hardening behavior was experimentally investigated by intermixing of (i) active fine-grained magnesia (MgO_A), (ii) dead-burned coarse magnesia (MgO_D) or inert quartz sand aggregates, (iii) citric acid, malic acid or acetic acid, and (iv) water. The effects of MgO purity, MgO reactivity and the type of organic additive on the evolution of hardening, Mg-organo salt formation, mineralogy and microstructure of the MgO intermixes were assessed by sound velocity measurements, XRD, FTIR spectroscopy, and electron microscopy. The reactivity of MgO_A controls the overall hardening behavior of the MgO intermixes but is strongly affected by the type and spatial distribution of the solid Mg-organo binder. MgO intermixes prepared with citric and malic acid result in stronger hardening compared to those based on acetic acid, which is caused by the interconnecting Mg-Hcitrate and Mg-malate binders vs spatially restricted and compact Mg-acetate encapsulation in micropores. MgO_D with low purity degree yields in stronger hardening, which is due to the high reactivity of accessory solid phases, such as merwinite, magnesioferrite and larnite, forming additional Ca-Fe-Mg-organo binder phases. Systematics in the above MgO-H2 O-organo systems are discussed in the scope of hardening reaction mechanisms of castables inferred by type and compositions of distinct MgO and carboxylic acids.